(untitled) (diségno, 2024)
This valuable volume is part of the editorial series Architecture, Geometry, and Astronomy, edited by the same editors [1]. It documents the outcomes of the second international studies day: Representing Time. Architecture, Geometry, Astronomy, held at palazzo Gravina on the premises of the Department of Architecture, University of Naples Federico II on June 9, 2023. [read more]